ANALISIS PENERAPAN METODE PENYUSUTAN DAN DAMPAKNYA TERHADAP LABA DI PT. TANAH LAUT Tbk PERIODE 2011-2018 - Daniel Nicson Simanjuntak (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
This study aims to determine how the application of the depreciation method in a company and its impact on company profits. The research was conducted using secondary data, namely the financial statements of PT. TANAH LAUT Tbk. The method used in this study is a descriptive method to obtain the data and information needed to achieve the research objectives. The analysis used in this study is to compare the depreciation method between the double-declining balance method and the straight-line method. Based on the research results obtained, the use of the straight-line depreciation method results in the amount of profit after depreciation being greater than the double-declining balance depreciation method in the first 3 years. However, since the fourth year, using the straight-line depreciation method will result in a smaller profit after depreciation, compared to the double-declining balance method. Seen from the amount of profit after depreciation in 2011 amounted to Rp. 3,000,144,989,- > Rp. 2,823,594,989,-. Total profit after depreciation in 2012 was Rp. 23.160.126.730,- > Rp. 23.071.851.730,-. Likewise, the amount of profit after depreciation in 2013 was Rp. 29,103,964,898,- > Rp. 29,081,896,148,-. Keywords : Depreciation Method, Company Profit.